Study on the Use of Several Types of Mulch on the Growth and Production of Long Beans (Vigna sinensis L.) - Anti, Wa Ode; Rahim, Abdul; Samiati, Samiati; Sifa, Muhammad; Santika, Jeksen (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2024)
This research aims to examine the effect of using several types of mulch on the growth and production of long beans. Additionally, it aims to determine which type of mulch provides the best growth and production for long beans. The research was conducted in Suka Damai Village, Central Tiworo District, West Muna Regency, Southeast Sulawesi Province. The materials used in this research included long bean seeds, cow manure, straw mulch, coconut fiber mulch, reed mulch, krinyuh mulch, and pesticides. The tools used consisted of machetes, hoes, analytical scales, meters, gembors, sprayers, buckets, raffia ropes, and writing tools. The research was structured based on a Randomized Block Design (RAK) which included five levels of mulch type treatment (M), namely without mulch (M0), straw mulch (M1), coconut fiber mulch (M2), reed mulch (M3), and crunchy mulch (M4). The variables observed included plant length (cm), number of productive branches (branches), number of fruits, fruit length, fresh fruit weight per plant (g), and production (t/ha). The data obtained was quantitatively analyzed using analysis of variance (ANOVA). If the analysis results show that the calculated F-value is greater than the F-table value, then the Honestly Significant Difference (BNJ) test is conducted at a 95% confidence level. The research results showed that the type of mulch treatment had a very significant effect on plant length, number of branches, number of fruits, fruit length, fresh fruit weight, and production. The krinyuh mulch type provided the best growth and production for long beans, with an average production reaching 23.83 t/ha